Pengaruh Modal Usaha dan Kualitas Produk Terhadap Kinerja UMKM dengan Kompetensi Kewirausahaan Sebagai Variabel Intervening - Millah, Aep Syaeful; Yusuf, Ayus Ahmad; Jaelani, Aan (CV. Strata Persada Academia, 2024)
Micro, Small and Medium Enterprises (MSMEs) in Indonesia hold a paramount position in national economic advancement, serving as the backbone of the economy and playing a crucial role in fostering economic growth. The performance of these enterprises can be evaluated based on their business capital, product standards, and entrepreneurial skills. This study delves into the impact of business capital and product quality on MSME performance, mediated by entrepreneurial competence, specifically within Kuningan District/Regency. Employing a quantitative research approach, the study targets MSME operators, particularly those engaged in food production, with a sample size of 85 respondents. The findings reveal that business capital and product quality collectively positively and significantly influence MSME performance. Furthermore, when analyzed individually, both factors significantly impact MSME performance. Moreover, business capital and product quality positively and significantly affect MSME performance through their influence on entrepreneurial competence. Ultimately, entrepreneurial competence emerges as a critical determinant of MSME performance, displaying a positive and significant relationship with overall business success.